Exploring Myanmar EFL Teachers' Perceptions, Practices and Challenges Toward the Use of AI Writing Tools - Yu, War War; Wilang, Jeffrey Dawala (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2025)
Artificial intelligence (AI) tools are becoming increasingly widespread in EFL classrooms as many applications support students in various aspects of language learning. Consequently, many EFL teachers are adapting to and embracing AI as a practical aid in their teaching. This study investigates Myanmar EFL teachers' perceptions of AI writing tools, their integration into teaching practices, and the challenges encountered in their use. A phenomenological research design was adopted, and qualitative data were collected through semi-structured interviews with ten Myanmar EFL teachers. The data technique used in this study was thematic analysis. The findings reveal that teachers utilize AI writing tools for student assessment, facilitating the learning process, sourcing writing materials, and planning lessons. While AI writing tools are perceived as beneficial for both students and teachers, concerns remain about their potential negative impact on students' writing skills and overall language development. Additionally, teachers face significant challenges in integrating AI writing tools due to issues such as internet instability, power outages, and limited technological knowledge. This study provides insights into the role of AI writing tools in EFL instruction in Myanmar and elsewhere, highlighting the need for improved technological infrastructure and teacher training to maximize their effectiveness.